Nutritional Status of Underfives at Balimbingan PTP VIII Simalungun Residence of North Sumatra - Erdanini Erdanini; Riza Iriani Nasution; Endang D. Hamid; Rusdidjas Rusdidjas (Indonesian Pediatric Society, 1997)
A cross sectional study was done on nutritional status of underfives at Balimbingan PTP VIII Simalungun residence of North Sumatra in 1992. The sample consisted of randomly selected 237 children, most of them were between 1-3 years age. Data were collected by using a questionnaire, physical examination, and anthroÂpometric measurement. Using weight for age parameter, the percentages of children with good to moderately nourished, mildly malnourished, and severely malnourished were 69.6%, 23.7%, and 6.7%, respectively. Using height for age parameter, the perÂcentages were 68.8%, 21.1%, and 10.1%, respectively. About half of the babies were breast-fed after 24 hours and 32,5% was breastfed at the age of 1-12 hours. There were 132 (78.1%) babies who got milk formula at the age of less than 4 months; of which 63.9% were given very diluted formula. Most babies (68%) were already given solid food at the age of less than 4 months. The relationship between number of chilÂdren with nutritional status of underfives was statistically significant (p<0.05), however there was no relationship between nutritional status with parents' education, formula feeding, and time at which solid food was given.